2011
DOI: 10.1007/s00586-011-2083-0
|View full text |Cite
|
Sign up to set email alerts
|

Complications and outcomes of posterior fusion in children with atlantoaxial instability

Abstract: Introduction Atlantoaxial instability (AAI) is an uncommon disease in children. Surgical treatment of pediatric patients with AAI poses a challenge to spine surgeons because of the patients' immature bone quality, extensive anatomical variability, and smaller osseous structures. In this study, the authors report complications and outcomes after posterior fusion in children with AAI. MethodsThe authors reviewed medical records of patients 13 years old and younger with AAI who underwent posterior fusion in the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 34 publications
(50 reference statements)
1
29
0
2
Order By: Relevance
“…Several articles stated that the dimensions of the cervical canal had reached adult size by 5-6 years of age [32,33]. Several studies detected that cervical lordosis increased after occipitocervical fusion [17,34,35]. Nevertheless, in the case of short-segment fixation at the C1-C2 level, Gluf and Brockmeyer [24] reported that the C1-C2 transarticular screw technique did not induce growth deformity in the sagittal or coronal plane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several articles stated that the dimensions of the cervical canal had reached adult size by 5-6 years of age [32,33]. Several studies detected that cervical lordosis increased after occipitocervical fusion [17,34,35]. Nevertheless, in the case of short-segment fixation at the C1-C2 level, Gluf and Brockmeyer [24] reported that the C1-C2 transarticular screw technique did not induce growth deformity in the sagittal or coronal plane.…”
Section: Discussionmentioning
confidence: 99%
“…Anderson et al [36] reported an increase in lordosis in pediatric patients undergoing C1-C2 transarticular screw fixation, although this was not statistically significant. Tauchi et al [35] showed that the height of the disc decreased at the fused level, but no different from the vertebra between the fused and nonfused levels. In our study, 16 patients were followed up for a period of 6-80 months, with no crankshaft phenomenon having been identified by the final visit.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,5,7,10,13,14,16,17,[23][24][25] Patients undergoing spinal arthrodesis are at significant risk for developing complications and having unplanned readmissions and/ or reoperations. These clinical outcomes are undesirable for patients, physicians, and the health care system in general, as they can result in increased cost and decreased quality of life.…”
Section: Neurosurg Focus 43 (4):e7 2017mentioning
confidence: 99%
“…patients 1,2,7,16,17,[23][24][25] or a single complication, 5,10,[13][14][15] while others have been limited to single centers 5,7,9,10 or to the adult population. 7,18,20,21 Few studies have provided a comprehensive description of patient characteristics, operative factors, and comorbidities on short-term morbidity and mortality after spinal arthrodesis in children.…”
mentioning
confidence: 99%
“…138 Based on our review of the literature, 23 years passed before there was another published article regarding OCF using allograft in children following Koop's publication, and 17 years passed before another article described allograft use for PCF in children following Stabler's article. 11,82,138,140 While there was a dearth of publications related to the use of allograft in pediatric cervical spine fusions for the 2 decades that followed the early failures reported in the 1980s, there has been a resurgence in interest over the most recent decade corresponding to the widespread use of rigid internal fixation techniques and the availability of BMP. 56,69,73,78,88,151 Emboldened by the greater fusion rates associated with screw-based constructs, with or without the use of BMP, there has been a sharp rise in publications describing OCF and PCF in children and adults.…”
Section: Publication Biasmentioning
confidence: 99%